(untitled) (Asian Journal of Agriculture, 2025)
Abstract. Esgrina FJO, Tan RJ. 2025. Growth vitamin hormone and shading intensity affect the rhizo-caulogenesis of etiolated avocado microclonal rootstocks. Asian J Agric 9: 160-173. The propagation of avocado clonal rootstocks is essential for a resilient, productive, and quality commercial cultivation. Optimizing growth conditions, particularly shading intensity and vitamin hormone concentration, plays a critical role in enhancing rhizogenesis, caulogenesis, and other physiological traits. Despite substantial research, the combined effects of these factors remain insufficiently explored. Thus, this study investigated the effects of shading intensity (40, 60, and 80%) and vitamin hormone concentrations (0, 0.1, 0.2, and 0.3 mL/L of water) on key morphological and physiological parameters of etiolated avocado clonal rootstocks, using a split-plot arrangement in randomized complete block design. The results revealed significant interaction effects (1%, Tukeys’ HSD) between shading intensity and hormone concentration in all parameters. The highest root number (1.33), root length (0.53 cm), chlorophyll content (61.10 SPAD), fresh weight (25.53 g), dry weight (10.33 g), were observed under 80% shading with 0.2-0.3 mL of vitamin growth hormone/L of water. Moderate shading (60%) combined with 0.1-0.2 mL of vitamin growth hormone promoted stem elongation (25.81 cm), and leaf area (100.99 cm²). These findings underscore the necessity of tailoring propagation protocols to specific environmental and hormonal conditions. The study provides comprehensive insights into optimizing avocado rootstock propagation, contributing to sustainable agricultural practices and supporting the growing global demand for avocados.